THE APPLICATION OF ECO ENZYME BIOTECHNOLOGY AS WASTE MANAGEMENT ORGANIC FOR PREPARATION THE DEVELOPMENT OF TALANG LAKE TOURISM KABUPATEN SOLOK WEST SUMATERA - Siska Alicia Farma (Pelita Eksakta, 2022)
Talang Lake is located in the Nagari area of Kampung Batu Dalam Subdistrict The Twin Lakes of Solok Regency. A driving force for the development of tourist villages is called groups Tourism Awareness (POKDARWIS). A frequently reported problem for tourist areas is the increasing volume of waste originating from tourists. One solution to overcome the problem of organic waste, especially food waste is to turn the waste into an ecoenzyme. Ecoenzyme is an organic solution that produced from simple fermentation of fresh vegetables and fruit peel waste, brown sugar and water. Ecoenzyme could be used to hand sanitizer and disinfectant, that one of the most needed products during this COVID-19 pandemic. Ecoenzyme also has the potential to become organic fertilizer solutions for agriculture so as to reduce the use of chemical fertilizers, vegetable and fruit yields better and the environment is not polluted. Ecoenzymes can help the maintenance sanitation and control of lake water quality. So that ecoenzyme has the potential to save expenses and earn additional income public. Through the use of biotechnology ecoenzyme is expected to be a preventive effort for the development of tourist villages through good and useful waste management. Based on the feedback was given, in general, people feel very satisfied and know that organic waste can great benefit to life.